Reform or transform? A spectrum of stances towards the economic status quo within ‘new economics’ discourses - Sam J. Buckton; Jasper O. Kenter; Nibedita Mukherjee; Sandra Waddock; Annela Anger-Kraavi; Simone Martino; Ioan Fazey; Adam P. Hejnowicz; Jane Kabubo-Mariara; Jordan O. Lafayette; Kristen Locy; Chris Scarr (Global Social Challenges Journal)
‘New economics’ discourses – comprising diverse approaches advocated as more just and sustainable replacements of dominant neoclassical and neoliberal economic perspectives – have been criticised as insufficiently coherent to form the ‘discourse coalitions’ necessary to enter the mainstream. To date there has been little systematic exploration of the agreement or divergence in new economics discourses. Here, we conduct a qualitative systematised review of new economics literature in the context of the COVID-19 pandemic to analyse stances towards the economic status quo and the depth of change advocated in it, such as fundamental and systemic transformation or more superficial reformist or accepting types of change that mostly maintain current economic systems. We interpreted authors’ stances towards six key status quo themes: capitalism; neoliberalism; GDP-based economic growth; debt-based money; globalisation; and the Sustainable Development Goals (SDGs). In the 525 documents analysed, there was relative consensus that neoliberalism needed transforming, stances towards GDP-based growth substantially diverged (from transformative to reformist/accepting), and stances towards the SDGs were mostly accepting, although the status quo themes tended to be infrequently mentioned overall. Different new economics approaches were associated with diverging stances. We suggest that alignment against neoliberalism and towards the SDGs may provide strategic coalescing points for new economics. Because stances towards core problematised aspects of mainstream economics were often not articulated, we encourage new economics scholars and practitioners to remain explicit, aware and reflexive with regard to the economic status quo, as well as strategic in their approach to seeking economic transformation.